Uganda : 2004 Article IV Consultation, Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria-Staff Report; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report ;, 2005)
This paper examines Uganda's 2004 Article IV Consultation, Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), and a Request for Waiver of Performance Criteria. The performance under the program supported by the PRGF was mixed. Four quantitative performance criteria for end-June 2004 were missed. Although two structural performance criteria for June and September were met, eight out of ten benchmarks were missed. The authorities are requesting waivers for nonobservance of the four performance criteria based on corrective actions, including eight prior actions.